UMP and UMK undergraduates infusing interest in STREAM among pupils - UMP, PNC (2019)
A total of 40 undergraduates from Universiti Malaysia Pahang (UMP) and Universiti Malaysia Kelantan (UMK) joined forces to carry out a programme, ‘Life and Journey@Pengkalan Chepa’, aimed at creating interest on science and technology among pupils at SK Pengkalan Chepa in Kota Bharu, Kelantan.